Our independence and the constitution - Fisher, Dorothy Canfield, 1879-1958. (New York : Random House, 1987)
Portrays the writing of the Declaration of Independence and the formation of the Constitution through the eyes of one Philadelphia family.
Reprint. Originally published: New York : Random House, 1950.
Keywords: United States; United States; Constitutions -- United States -- Juvenile literature; Constitutional history -- United States -- Juvenile literature; Constitutional history -- United States; United States -- Politics and government -- 1775-1783 -- Juvenile literature; United States -- Politics and government -- 1775-1783.